Using Virtual AChE Homology Screening to Identify Small Molecules With the Ability to Inhibit Marine Biofouling - Arabshahi, Homayon John; Trobec, Tomaž; Foulon, Valentin; Hellio, Claire; Frangež, Robert; Sepčić, Kristina; Cahill, Patrick; Svenson, Johan (Frontiers in Marine Science, 2021)
The search for effective yet environmentally friendly strategies to prevent marine biofouling is hampered by the large taxonomic diversity amongst the fouling organisms and a lack of well-defined conserved molecular targets. The acetylcholinesterase enzyme catalyses the breakdown of the neurotransmitter acetylcholine, and several natural antifouling allelochemicals have been reported to display acetylcholinesterase inhibitory activity. Our study is focussed on establishing if acetylcholinesterase can be used as a well-defined molecular target to accelerate the discovery and development of novel antifoulants via sequential high-throughput in silico screening, in vitro enzymatic studies of identified compound libraries, and in vivo assessment of the most promising lead compounds. Using this approach, we identified potent acetylcholinesterase inhibitors with IC50 values down to 3 μM from a 10,000 compound library. The most potent inhibitors were screened against five microfouling marine bacteria and marine microalgae and the macrofouling tunicate Ciona savignyi. No activity was seen against the microfoulers but a potent novel inhibitor of tunicate settlement and metamorphosis was discovered. Although only one of the identified active cholinesterase inhibitors displayed antifouling activity suggesting the link between cholinesterase inhibition and antifouling is to be limited to certain compound classes, the study is highlights how in silico screening employed regularly for drug discovery can also facilitate discovery of antifouling leads.